2014
DOI: 10.4049/jimmunol.1400368
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role for the NLRP3 Inflammasome during Acute Lung Injury

Abstract: The inflammasome is a key factor in innate immunity and senses soluble pathogen and danger associated molecular patterns as well as biological crystals (urate, cholesterol, etc.), resulting in expression of IL-1β and IL-18. Using a standard model of acute lung injury (ALI) in mice featuring airway instillation of LPS, ALI was dependent on availability of NLRP3 as well as caspase-1, which are known features of the NLRP3 inflammasome. The appearance of IL-1β, a product of NLRP3 inflammasome activation, was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
220
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(256 citation statements)
references
References 41 publications
13
220
1
2
Order By: Relevance
“…instillation of LPS stimulates airway epithelial cells to release proinflammatory cytokines, such as IL-1β and TNF-α, which causes subsequent neutrophilic infiltration and ultimately results in lung tissue injury in an LPS-induced ALI mouse model. In a recent study, knockout mice in an NLRP3 inflammasome component showed lower level of immune cell recruitment such as neutrophils in an LPS-induced ALI mouse model than wild-type mice (Grailer et al, 2014). Therefore, we extended our work to the ALI in vivo mouse model to support our in vitro data.…”
Section: It Inhibited Cell Recruitment In the Ali Mouse Modelsupporting
confidence: 78%
See 1 more Smart Citation
“…instillation of LPS stimulates airway epithelial cells to release proinflammatory cytokines, such as IL-1β and TNF-α, which causes subsequent neutrophilic infiltration and ultimately results in lung tissue injury in an LPS-induced ALI mouse model. In a recent study, knockout mice in an NLRP3 inflammasome component showed lower level of immune cell recruitment such as neutrophils in an LPS-induced ALI mouse model than wild-type mice (Grailer et al, 2014). Therefore, we extended our work to the ALI in vivo mouse model to support our in vitro data.…”
Section: It Inhibited Cell Recruitment In the Ali Mouse Modelsupporting
confidence: 78%
“…LPS-induced ALI model was used as described previously (Grailer et al, 2014;Shim et al, 2013). Briefly, LPS (5 mg/kg) was instilled intranasally (i.n.)…”
Section: Lps-induced Ali Mouse Modelmentioning
confidence: 99%
“…In the context of these previous findings, we hypothesized that the IL-23-induced decrease in Bcl-2 might result in enhanced ROS generation, which in turn would further drive apoptosis susceptibility in macrophages exposed to athero-relevant pro-apoptotic factors. To address this hypothesis, we incubated macrophages with 7KC in the absence or presence of IL-23 and then probed the cells with CellROX Deep Red ™ , which fluoresces in the cytoplasm when exposed to ROS 43 . Similar to the apoptosis findings, IL-23 alone did not induce ROS in macrophages, but it enhanced ROS in the presence of 7KC (Figure 8A and Online Figure XXIIIA).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown IL-9 (38), TNF (39), and chemokine (40) production by neutrophils in response to RSV. Neutrophils are a source of IL-1␤ in lung injury models (41), but this is the first study that has demonstrated IL-1␤ production by neutrophils in response to respiratory viral infection. Airway neutrophilia is observed in patients with bronchiolitis (42), and an increase in neutrophils is detected in blood prior to the influx of CD8 T cells (43).…”
Section: Discussionmentioning
confidence: 99%